(untitled) (Journal of Science and Technology, 2015)
The major contribution made in the organization is that social groups and popular organizations should operate as co-operatives were possible. These co-operatives can be used to (i) achieve increased domestic production of food, industrial raw materials and manufactured products; (ii) contribute to the process of making decisions which affect the lives of the masses; (iii) assist in instilling discipline and professional ethnics in the members of the different organizations and the community.